Analisis Kelayakan Ekspansi Warung Makan “Salsabila” - Anvaulauvaa R, Rayvivant; Priambudi, Tunggul Wibisono; Nugraha, Oric Cipta; Purwati, Purwati; Inggarwati, Komala (Jurnal Pengabdian dan Kewirausahaan, 2024)
This research discusses the potential for expansion of the "Salsabila" as an UMKM actor into a modern cafe during the post-pandemic era. This research uses quantitative and qualitative data collection methods and quantitative descriptive analysis data processing which will be formulated into numbers. The research results show that the expansion shows positive potential based on financial and market aspects. The decline in F&B growth rate after the pandemic is considered not to affect the potential of the F&B industry. This is indicated by the annual increase in the real income of the creative industry in 2017-2021. Apart from that, the payback period, IRR and NPV of this expansion show a positive value or can be said to be feasible in terms of investment value analysis.